MELIA AZEDARACH L. (MELIACEAE): PHYTOCHEMICAL ANALYSIS AND EVALUATION OF ANTIBACTERIAL ACTIVITY OF FRUIT EXTRACTS. - Masuku , Phakamani Linda; Baijnath, Himansu; Singh, Karishma (Student's Journal of Health Research Africa, 2024)
Background Medicinal plants are still the main source of therapeutic substances for treating infectious diseases that seriously endanger human health in South Africa. The current study examined the potential therapeutic applications of the young, ripe, and mature fruits of M. azedarach. Methods A standard protocol, which included chemical reagents and a series of reactions, was used to determine the presence of the phytochemical compound classes. The methanol and hexane extract of young, ripe, and mature fruits were applied to six bacterial strains (Methicillin-resistant Staphylococcus aureus (MRSA), Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli, Salmonella typhimurium, and Staphylococcus aureus) to evaluate their antibacterial activity. Results Methanol extracts of young, ripe, and mature fruits tested positive for six bioactive compounds. Hexane extracts of young, ripe, and mature fruits tested positive for four bioactive compounds. All six bacterial strains were highly susceptible to the methanol extract of fruits. Klebsiella pneumoniae and P. aeruginosa were strongly resistant to hexane extracts of the young fruits. Klebsiella pneumoniae, E. coli, MRSA, and P. aeruginosa were strongly resistant to hexane extracts of the ripe fruits. Klebsiella pneumonia and E. coli were strongly resistant to hexane extracts of the mature fruits. Conclusion Melia azedarach fruits, whether young, ripe, or mature, contain bioactive therapeutic compounds (Carbohydrates, Amino acids, Alkaloids, Flavonoids, Saponins, Sterols, Steroids/Terpenoids, Phenols, Mucilage and Gums, Fixed oils, and fats) that can be used to develop medicines to treat various human ailments and display strong antibacterial potential. Recommendations Future research is needed to evaluate each bioactive compound's antibacterial activity and efficacy to determine which can be used as components in producing antibacterial medicines and drugs.